Visceral Leishmaniasis in Southwestern Iran: A Retrospective Clinico-Hematological Analysis of 380 Consecutive Hospitalized Cases (1999-2014). - Bahador Sarkari; Tahereh Naraki; Mohammad Amin Ghatee; Samaneh Abdolahi Khabisi; Mohammad Hassan Davami (PLoS ONE)
Visceral Leishmaniasis (VL) is an endemic parasitic disease and remains as a major health concern in southwestern Iran. The current study describes clinico-hematological, epidemiological and therapeutic features of VL cases, admitted to university-affiliated hospitals, during 1999-2014 in Fars province, southwestern Iran. A total of 380 VL cases were recorded during a 16 years period, giving an average annual admission of 23.75 cases/year in which 217 (57.1%) were male and 163 (42.9%) were female. Mean age of the patients was 3.7 years. The majority of the cases (91.5%) were ≤ 5 years old. Bone-marrow aspiration detected Leishmania amastigotes only in 26.6% of cases. Fever (98.1%), abdominal protrusion (65.1%) and hepatosplenomegaly (63.7%) were the most common clinical presentations of the patients. Pancytopenia was noted in 43.1, anemia in 87.3 and thrombocytopenia in 64% of cases. Increase in the level of AST (aspartate aminotransferase), ALT (alanine aminotransferase), alkaline phosphatase, LDH (lactate dehydrogenase) and CRP (C-Reactive Proteins) were seen in 84.9, 53.6, 44.4, 72.5 and 83.1% of cases, respectively. Mortality was noted in 5.3% of cases. Deranged haemato-biochemical parameters including total and direct bilirubin, PLT (platelet) and pancytopenia were significantly contributed to mortality from VL. Moreover, clinical features such as severe splenomegaly as well as bacterial infections were meaningfully contributed to death from VL. The majority of patients (74.9%) were treated with meglumine antimoniate. Amphotericin B was administrated in 59 of cases, 11 of them were initially treated with meglumine antimoniate with a shift to amphotericin B, because of treatment failure. Findings of the current study demonstrated that VL is present in southwest of Iran with a fairly continual rate during the last 16 years period. Deranged haemato-biochemical parameters along with severe splenomegaly contributed to mortality from VL.